Thrown into crisis? German-American relations in a period of strategic change - Peter Rudolf (Stiftung Wissenschaft und Politik (SWP), 2002)
Recent tensions at the governmental level do not yet add up to a crisis in GermanAmerican relations. But political divergences and dissonances are an expression of structural conflicts in the transatlantic relationship that have been intensified by the post-September 11 strategy shift in American global policy. The emerging paradigm shift in U.S. foreign policy confronts Germany's policy toward the United States with new challenges. These challenges cannot be mastered through either unreflective opposition or reflexive loyalty; rather, they require a strategically conscious approach toward the United States.(SWP Comments / SWP)
Keywords: 320